Spindle Cell Carcinoma of Oral Cavity: A Rare Entity (Bangladesh Journal of Medical Science, 2021)
Introduction:Spindle cell carcinomas (SpCC) are a rare variant of squamous cell carcinoma which is rarely encountered in the head and neck. It is also known as“pseudocarcinoma”, “sarcomatoidcarcinoma,” and “carcinosarcoma”.It has an aggressive nature and has poor prognosis despite aggressive treatment.Case report: A 48-year-old lady presented to us with a right painless upper gum swelling which was progressively enlarging for 3 months after tooth extraction. Examination of the oral a fungating mass over the right upper alveolus extending to the right upper gingivolabial sulcus. She was subjected to a debulking palliative to reduce the tumour bulk. The intraoperative samples sent for histopathological examination was reported as SpCC, AJCC (8th edition) stage pT2pN3b. She recovered well after the surgery with quality of life after the surgery.Bangladesh Journal of Medical Science Vol.20(4) 2021 p.923-925